Jesús Arroyo Alejandre. El abandono rural. México : Universidad de Guadalajara, 1989. 260 p. - Morelos, José B. (Estudios Demográficos y Urbanos, 1990)
Jesús Arroyo Alejandre, EJ abandono rural. Universidad de Guadalajara, México, 1989.